Elevated oxytocin and noradrenaline indicate higher stress levels in allergic rhinitis patients: Implications for the skin prick diagnosis in a pilot study. - Jelena Gotovina; Christina L Pranger; Annika N Jensen; Stefanie Wagner; Oswald D Kothgassner; Nadine Mothes-Luksch; Rupert Palme; Desirée Larenas-Linnemann; Jaswinder Singh; Ralph Mösges; Anna Felnhofer; Lisa-Maria Glenk; et al. (PLoS ONE, 2018)
The effects of acute stress on allergic symptoms are little understood. The intention of this clinical study was to study the effects of acute stress and related mediators in allergic rhinitis (AR), taking the wheal and flare reaction in skin prick testing (SPT) as a readout.19 healthy and 21 AR patients were first subjected to SPTs with grass pollen-, birch pollen- and house dust mite allergen extracts, histamine and negative control. Subsequently, participants were exposed to a standardized Trier Social Stress Test (TSST), followed by SPT on the contralateral forearm. Stress responders were identified based on the salivary cortisol levels and State-subscale of State-Trait-Anxiety Inventory (STAI-S). Blood samples were collected before and after TSST and adrenaline, noradrenaline, serotonin, oxytocin, platelet activating factor and prostaglandin D2 were analyzed by enzyme immunoassay (EIA).SPT results of 14/21 allergics and 11/19 healthy who responded with stress after TSST were evaluated. No significant differences regarding SPT to allergens or histamine before and after the stress test could be calculated at the group level. But, the wheal and flare sizes after TSST increased or decreased substantially in several individuals, and unmasked sensitization in one "healthy" person, which could not be correlated with any mediator tested. The most significant finding, however, was that, independent of TSST, the baseline levels of oxytocin and noradrenaline were significantly higher in allergics.High baseline levels of noradrenaline points toward higher stress levels in allergic patients, which might be counterregulated by elevated oxytocin. Moreover, our data indicate that acute stress may have a significant influence on SPT fidelity in susceptible individuals.